Preparation and characterization of APTES-functionalized graphene oxide for CO2 adsorption - Nur Fatihah, Tajul Arifin; Nur Azira Natasha, Zulkipli; Norhaniza, Yusof; Ahmad Fauzi, Ismail; Farhana, Aziz; Wan Norharyati, Wan Salleh; Juhana, Jaafar; Nik Abdul Hadi, Md Nordin; Norazlianie, Sazali (Akademi Baru, 2019)
The increase of carbon dioxide (CO2) concentrations in the atmosphere is one of alarming issues nowadays. Thus, development and optimization of new solid adsorbents is highly demanded for the establishment of energy-efficient and high-throughput CO2 capture processes in industry. Herein, graphene oxide (GO) adsorbent was prepared and further functionalized by amine functionalization, 3-aminopropyl-triethoxysilane (APTES). GO was prepared using Modified Hummer’s Method followed by functionalization with APTES. GO and APTES-GO were characterized using Fourier Transmission Infrared Spectroscopy (FTIR), Raman spectroscopy, scanning electron microscope (SEM), and N2 adsorption isotherm. The N2 adsorption capacity for APTES. GO at 15 bar is the highest (179 mmol/g) compared to other lower pressures and pristine GO at any pressure. FTIR analysis showed significant peaks at 1474 cm−1 and 1440cm−1 indicating the presence of N-H and NH2 groups, respectively